Multiple Bone Metastases as the Initial Presentation of Occult Breast Carcinoma in a Kidney Transplant Recipient - Marina Kljajić; Guy Alush; Nikolina Bašić-Jukić (http://dharmais.co.id/, 2023)
Introduction: Due to their immunosuppressive medication regimen, solid organ transplant recipients have an increased risk of developing cancer, which might jeopardize their survival. Specifically, cardiovascular disease and malignancy are the two leading causes of death in kidney transplant recipients. In solid organ recipients, cutaneous malignancies, lymphomas, and Kaposi’s sarcomas also appear to be the most prevalent cancer forms. Thus, carcinoma of unknown primary origin is a clinical entity that diagnosing requires a high level of suspicion and thorough reviewing of laboratory, radiological, and clinical findings. Further, susceptible patients, such as immunocompromised ones, should merit a careful analysis of findings and detailed analytic rationale. We, therefore, present the following case report demonstrating the importance of follow-up of specific suspicious serum markers in transplant patients. To our knowledge, this study is the first case to report an occult breast carcinoma as the initial presentation in a patient with a kidney transplant.Case Presentation: In the following case, the primary indication for malignancy was elevated alkaline phosphatase (ALP), a common finding in patients with chronic renal failure. Once noticed in a scheduled post-transplantation follow-up, further diagnostic tests, such as a broader serum panel, sternal puncture, and mammography, were ordered and returned normal. Subsequently, CT was ordered and revealed lytic and sclerotic bone changes. Afterward, serum tumor markers were ordered together with gynecological ultrasound and PET-CT. Finally, an iliac bone marrow biopsy confirmed a breast cancer diagnosis of unknown primary origin, causing the elevated ALP.Conclusions: This case report presents a uniquely difficult diagnostic challenge as an expected elevated value of ALP in a kidney transplant recipient was the only diagnostic clue for occult breast carcinoma. We discuss further the vigilance that physicians must exert when dealing with kidney transplant recipients and the implication of carcinoma of unknown primary in this population.